Magnetic suppression of turbulence and the star formation activity of molecular clouds. Issue 4 (29th November 2017) - Zamora-Avilés, Manuel; Vázquez-Semadeni, Enrique; Körtgen, Bastian; Banerjee, Robi; Hartmann, Lee
Abstract: We present magnetohydrodynamic simulations aimed at studying the effect of the magnetic suppression of turbulence (generated through various instabilities during the formation of molecular clouds by converging) on the subsequent star formation (SF) activity. We study four magnetically supercritical models with magnetic field strengths B = 0, 1, 2, and 3 μG (corresponding to mass–to–flux ratios of ∞, 4.76, 2.38, and 1.59 times the critical value), with the magnetic field, initially being aligned with the flows. We find that, for increasing magnetic field strength, the clouds formed tend to be more massive, denser, less turbulent, and with higher SF activity. This causes the onset of SF activity in the non-magnetic or more weakly magnetized cases to be delayed by a few Myr in comparison to the more strongly magnetized cases. We attribute this behaviour to the suppression of the non-linear thin shell instability (NTSI) by the magnetic field, previously found by Heitsch and coworkers. This result is contrary to the standard notion that the magnetic field provides support to the clouds, thus reducing their star formation rate. However, our result is a completely non-linear one, and could not be foreseen from simple linear considerations.